(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper presents results of study aimed to evaluate issues of current development of bioenergy in Latvia, taking into account restrictions, which may affect future progress of main biomass sources. These restrictions are based on latest European Union (EU) regulations and recommendations; and worldwide concerns of scholars on sustainability, particularly environmental (e.g. biodiversity, ecosystem resilience, carbon sequestration) of bioenergy (biomass) development. The appropriate qualitative and quantitative research methods have been used in the process of study. The results of examination suggest that biomass possesses one of the greatest potentials for further increasing renewables production, particularly in Latvia. The characteristics and perspectives of main biomass sources’ development are assessed for compliance with the EU latest regulations, recommendations and policies, particularly Common Agricultural Policy (CAP) 2014-2020, and they demonstrate [reveal?] several limitations. The restrictions under the CAP regulations’ so-called ‘greening’ requirements mainly affect the production of energy crops, limiting monocultures’ growing. For some types of biomass production (e.g. energy cultures, wood biomass), several limitations or restrictions are considered, in particular, those related to environmental issues such as biodiversity, soil properties, agro-ecosystems and landscape. Forest origin, non-food plants (e.g. perennial grasses) and different kind of residues and waste could be the most important, perspective and sustainable biomass sources in Latvia. Besides, the dominance of a single bioenergy source would be unsustainable in the long run, and diversifying of the energy system is preferred.